Relevance between Proximal Humeral Migration and Rotator Cuff Tears - Zhang, Yichong; Chen, Jianhai; Ma, Mingtai; Ju, Jiabao; Jiang, Baoguo; Zhang, Peixun (Frontiers in Surgery, 2022)
Background Proximal humeral migration is common in patients with rotator cuff tears. In this study, we aimed to evaluate the relevance between proximal humeral migration and some rotator cuff tear-related factors. Methods A total of 75 patients with unilateral rotator cuff tears were retrospectively included from August 2016 to January 2018 who underwent magnetic resonance imaging and X-ray examinations before enrollment. We introduced the upward migration index (UMI) to stratify the patients into three groups, Group A: 1 < UMI ≤ 1.3; Group B: 1.3 < UMI ≤ 1.4; and Group C: UMI > 1.4. Pearson correlation analysis and logistic regression analysis were used to evaluate the relationship between UMI and age, sex, body mass index, pain, fatty degeneration grade, tear size, and thickness of ruptured tendon. Then, the χ2 test and receiver operator characteristic curve were applied to measure the diagnostic value of UMI. Results The average UMI was 1.34 ± 0.07, ranging from 1.16 to 1.48. For the Pearson correlation analysis, there was a negative correlation between UMI and tear size (R = −0.68, p < 0.01), and also, there was a negative correlation between UMI and the visual analogue scale score (R = 0.342, p < 0.01). What is more, there was a negative correlation between UMI and the fatty degeneration grade (R = −0.373, p < 0.01). Ordinal multinomial logistic regression analysis indicated that tear size (β = −1.825, p < 0.001) was the independent predictor of UMI, which was a risk factor for humeral upward migration. The cutoff points of UMI were 1.38 and 1.3 to determine tears and distinguish large tears from small ones. Conclusions UMI is a good predictor for humeral upward migration, which is related to the tear size of posterosuperior cuff tears. When the UMI is <1.3, a large tear should be alerted. Combining physical examination and X-ray is helpful for evaluating rotator cuff tears.